Respuesta :
Answer:
[tex]\mathbf{f(22) = \dfrac{1}{729}}[/tex]
[tex]\mathbf{f(0) = \dfrac{1}{(25)}}[/tex]
[tex]\mathbf {f(a) = \dfrac{1}{(a+5)^2}}}[/tex]
[tex]\mathbf{f(t+22) = \dfrac{1}{(t+27)^2}}[/tex]
[tex]\mathbf{f(x+h) = \dfrac{1}{(x+h+5)^2}}[/tex]
[tex]\dfrac{f(x+h)-f(x)}{h}[/tex]= [tex]\mathbf{ \dfrac{-h-2x-10}{(x+h+5)^2(x+5)^2}}[/tex]
Step-by-step explanation:
The mathematical interpretation of the A function f is given by
f(x)equals=StartFraction 1 Over left parenthesis x plus 5 right parenthesis squared End Fraction 1(x+5)2 is :
[tex]f(x) = \dfrac{1}{(x+5)^2}[/tex]
So; we are ask to find the following:
a)
f(22) ; i.e what is the function when x = 22
So replacing x = 22 into the above function; we have:
[tex]f(x) = \dfrac{1}{(x+5)^2}[/tex]
[tex]f(22) = \dfrac{1}{(22+5)^2}[/tex]
[tex]f(22) = \dfrac{1}{(27)^2}[/tex]
[tex]\mathbf{f(22) = \dfrac{1}{729}}[/tex]
f(0) : i.e what is the function when x = 0
So replacing x = 0 into the given function; we have:
[tex]f(x) = \dfrac{1}{(x+5)^2}[/tex]
[tex]f(0) = \dfrac{1}{(0+5)^2}[/tex]
[tex]\mathbf{f(0) = \dfrac{1}{(25)}}[/tex]
f(a) : i.e what is the function when x = a
So replacing x = a into the given function; we have:
[tex]f(x) = \dfrac{1}{(x+5)^2}[/tex]
[tex]\mathbf {f(a) = \dfrac{1}{(a+5)^2}}}[/tex]
f(tplus+22), i.e what is the function when x = t+22
So replacing x = t+22 into the given function; we have:
[tex]f(x) = \dfrac{1}{(x+5)^2}[/tex]
[tex]f(t+22) = \dfrac{1}{(t+22+5)^2}[/tex]
[tex]\mathbf{f(t+22) = \dfrac{1}{(t+27)^2}}[/tex]
f(xplus+h), i.e what is the function when x =x+h
So replacing x = x+h into the given function; we have:
[tex]f(x) = \dfrac{1}{(x+5)^2}[/tex]
[tex]\mathbf{f(x+h) = \dfrac{1}{(x+h+5)^2}}[/tex]
Similarly; another function is given as :
Start Fraction f left parenthesis x plus h right parenthesis minus f left parenthesis x right parenthesis Over h End Fraction f(x+h)-f(x)h.
Mathematically the above function can be expressed as:
[tex]\dfrac{f(x+h)-f(x)}{h}[/tex]
where ;
[tex]f(x+h) = \dfrac{1}{(x+h+5)^2}[/tex] and [tex]f(x) = \dfrac{1}{(x+5)^2}[/tex]
So;
[tex]\dfrac{f(x+h)-f(x)}{h} = \dfrac{\dfrac{1}{(x+h+5)^2} -\dfrac{1}{(x+5)^2} }{h}[/tex]
[tex]=\dfrac{ \dfrac{(x+5^2)-(x+h+5)^2}{(x+h+5)^2(x+5)^2} }{h}[/tex]
[tex]= \dfrac{x^2+10x +25-x^2-h^2-25-2xh-10h -10x}{h(x+h+5)^2-(x+5)^2}[/tex]
[tex]= \dfrac{h(-h-2x-10)}{h(x+h+5)^2(x+5)^2}[/tex]
[tex]=\mathbf{ \dfrac{-h-2x-10}{(x+h+5)^2(x+5)^2}}[/tex]
b) Note that f could also be given by
f(x)equals=StartFraction 1 Over x squared plus 10 x plus 25 EndFraction
1×2+10x+25
Explain what this does to an input number x.
The mathematical expression of the function is:
[tex]f(x) = \dfrac{1}{(x^2+10x + 25)}[/tex]
the input = x ; so 5 is added to the i.e x+ 5;
After that the square of the entity (x+5) is taken giving rise to (x+5)²
then the reciprocal of the function is taken ; which now becomes:
[tex]f(x) = \dfrac{1}{(x+5)^2}[/tex]
If we expand the quadratic expression in the bracket; we have:
x being multiplied by the square ² which = x²
then x is multiplied by the addition of (5+5 )x to give 10x
Finally 5 is multiplied by the square ² which = 5² = 25
After the addition of all this three together ; the reciprocal was taken to get:
[tex]f(x) = \dfrac{1}{(x^2+10x + 25)}[/tex]